Manajemen Produksi Penyiaran Program “Sandiwara Radio Kos-Kosan Gayam” Geronimo FM - Yulinda Sari; Dyo Rizky; Puti Andam Sari (ETTISAL : Journal of Communication, 2017)
Radio Geronimo FM is one of the long standing radio in Yogyakarta city. As a long-standing radio, Geronimo FM Jogja radio is required to keep the audience with a tight competition along with the emergence of new radio. One of the strategies undertaken by Radio Geronimo FM Jogja in keeping the audience is by conducting broadcasting management. This study examines the implementation of radio broadcasting management Geronimo FM Jogja in keeping the audience. The method used is descriptive qualitative observed phenomena experienced by research subjects. This study uses qualitative research methods, which became the object of his research is Koskosan Gayam comedy program in Geronimo FM Yogyakarta. Data collection technique is done by interview, pre-production observation, production, and post-production of Radio Geronimo FM Jogja. The research subjects are Radio Programs Producer division Geronimo FM Jogja and Koskosan Gayam figures. Based on the results of this study is to show that there is a creative strategy Kosam Kosan Gayam which has been applied since the beginning of this event stand by lifting the existing phenomenon in boarding house with cultural diversity in it that is packed with comedy